Analisis Produksi dan Pendapatan Usahatani Jagung di Desa Piong Kecamatan Sanggar Kabupaten Bima - ANGGRIANI, RIKA; SUDARMA, I MADE; WIDHIANTHINI, WIDHIANTHINI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.12, No.2, Desember 2023, 2023)
Analysis Of Production And Income Of Corn Farming In Piong Village , Sanggar District , Bima Regency.  Piong Village, located in West Nusa Tenggara Province, is one area that has potential as a national corn producer because it has climatic conditions, soil types and topography that strongly support corn development. Corn agribusiness development is a regional commodity development program. The purpose of this study is to determine the factors that affect the production and income of corn farming.The population taken by the researchers in this study were all people who made a living as a corn farmer. The sample using the simple random sampling method is a random sampling based on place and anyone. Respondents in the study amounted to 38 people.The results of this study indicate that fthe factors thataffectThe production of corn farming in Piong Village, Sanggar District, Bima Regency is the area of ??land, seeds, fertilizers, pesticides and labor.The variable that have a significant effect on corn farming production are land area, seeds, fertilizers, pesticides and labor. Income received from corn farming in Piong Village, Sangar District, Bima Regency for one growing seasonamounting to Rp 25.885.717,00/Ha.